1999
DOI: 10.1177/0310057x9902700209
|View full text |Cite
|
Sign up to set email alerts
|

Sub-Tenon's Block: The Effect of Hyaluronidase on Speed of Onset and Block Quality

Abstract: The role of hyaluronidase on the onset time and quality of single quadrant sub-Tenon's block was studied in a prospective, randomized, double-blind controlled manner. One hundred and twenty consecutive patients undergoing cataract surgery under local anaesthesia received a sub-Tenon's block with either of two local anaesthetic solutions. One consisted of 2% plain lignocaine 3 ml with 0.5% plain bupivacaine 2 ml. The other consisted of 2% lignocaine 1 ml containing 150 IU per ml of hyaluronidase with 2% plain l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 5 publications
1
18
0
Order By: Relevance
“…There was no improvement in sensory blockade with the addition of hyaluronidase but in both groups the quality of the block was excellent. This supports the findings of a recent study by Guise and Laurent8 who showed significantly better akinesia after 9 minutes in the “with hyaluronidase” group compared with the control group. When they compared the quality of block at 13 minutes, however, they found no significant difference between the two groups.…”
Section: Discussionsupporting
confidence: 91%
“…There was no improvement in sensory blockade with the addition of hyaluronidase but in both groups the quality of the block was excellent. This supports the findings of a recent study by Guise and Laurent8 who showed significantly better akinesia after 9 minutes in the “with hyaluronidase” group compared with the control group. When they compared the quality of block at 13 minutes, however, they found no significant difference between the two groups.…”
Section: Discussionsupporting
confidence: 91%
“…Guise and Laurent20 performed an RCT using 30 IU ml −1 in a 5 ml sub-Tenon injection. Akinesia scores were improved at the time intervals 3–9 min after instillation of the block.…”
Section: Hyaluronidasementioning
confidence: 99%
“…However, as an adjuvant in retrobulbar and peribulbar anesthesia, 6,9,42 it enhances the onset of the block. It also improves the onset and quality of the block in the sub-Tenon procedure by promoting diffusion to the periorbital and retroorbital tissue 19,[43][44][45] and alleviating the need for a facial nerve block, which can be painful. 31,45 Hyaluronidase 6 helps to prevent a decrease in retinal circulation, an increase in intraocular pressure (IOP) and also reduce the risk for muscle toxicity from local anesthetic agents.…”
Section: Anesthetic Agentsmentioning
confidence: 99%